2016
DOI: 10.1186/s13046-016-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138 functions as a tumor suppressor in osteosarcoma by targeting differentiated embryonic chondrocyte gene 2

Abstract: BackgroundMicroRNA-138 (miR-138) has been proven to be a tumor suppressor gene in various types of tumors. However, the expression and the role of miR-138 in human osteosarcoma are still poorly understood. We investigated the function and the underlying mechanism of miR-138 in osteosarcoma.MethodsThe expression of miR-138 in human osteosarcoma tissues and cell lines was detected by real-time PCR analysis. The gain-of-function and loss-of-function experiments were performed on osteosarcoma cell lines to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…Recent studies have reported that miRNAs regulate endothelial cell apoptosis and senescence-related pro-inflammatory status [7,8]. MiR-138 is an important member of miRNA family and has been shown to be a tumour suppressor in many studies [9,10]. Interestingly, miR-138 was reported to contribute to endothelial cell dysfunction when induced by pro-inflammatory cytokines [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that miRNAs regulate endothelial cell apoptosis and senescence-related pro-inflammatory status [7,8]. MiR-138 is an important member of miRNA family and has been shown to be a tumour suppressor in many studies [9,10]. Interestingly, miR-138 was reported to contribute to endothelial cell dysfunction when induced by pro-inflammatory cytokines [3].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the tumors have metastasized to the lungs in patients diagnosed with osteosarcomas [4]. Standard neoadjuvant chemotherapy can effectively increase the possibility of limb salvage, which can significantly improve the 5-year survival rate and quality of life in patients with osteosarcomas [5]; however, intrinsic or acquired chemotherapy resistance affects the therapeutic effect [6][7][8]. Previous studies have shown that chemotherapy resistance of tumors is a complex and multistage process, including genes, proteins, miRNAs, and signaling pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the regulatory functions in normal cells, growing evidence has highlighted the important roles of microRNAs in various biological processes of cancers. Among the abundant microRNAs, miR-138 is a member studied extensively and considered as a tumor suppressor in many types of cancers (27,28). In non-small cell lung cancer, overexpression of miR-138 was found to inhibit the proliferation of cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%